Mechanism and Implementation Path of Digital Empowerment for the Public Service Supply of National Fitness for Disabled People (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Mechanism and Implementation Path of Digital Empowerment for the Public Service Supply of National Fitness for Disabled People